MicroRNA-21 Overexpression Promotes the Neuroprotective Efficacy of Mesenchymal Stem Cells for Treatment of Intracerebral Hemorrhage - Zhang, Heyu (Front Neurol, 2018)
Intracerebral hemorrhage (ICH) has high morbidity and mortality, with no effective treatment at present. One possible therapeutic strategy involves the use of mesenchymal stem cells (MSCs), which have shown promise in experimental models and have great potential for treating nervous illnesses in humans. However, many deficiencies in MSC treatment still need to be addressed, including their poor survival rate post-transplantation. Previously, we reported that the microRNA-21 (miR-21) is downregulated in ICH patients' blood and brain tissue. In this study, we aimed to examine its role and therapeutic efficacy in ICH using miR-21-overexpressing MSCs. We found that this microRNA can enhance MSC survival and recovery of neurological function in ICH rats. Its mechanism of action involves reduced neuronal apoptosis. In addition, we demonstrated that miR-21 can be transported to neurons through exosomes derived from MSCs and that it can target transient receptor potential melastatin 7 (TRPM7) to alleviate neuronal injury following ICH. We also observed that the NF-κB pathway is involved in the regulation of miR-21 in neural cells. In conclusion, miR-21 significantly enhances the survival of MSCs in ICH, and miR-21-overexpressing MSCs clearly improved neurological function in ICH rats. Transplantation of miR-21-overexpressing MSCs may, therefore, provide an effective strategy for neuroprotection and treatment of cerebrovascular diseases.